Structural transformations of 3-fluoro and 3-fluoro-4-methoxy benzaldehydes under cryogenic conditions: A computational and low temperature infrared spectroscopy investigation - Konarska, Jadwiga; Fausto, Rui; ILDIZ, GÜLCE ÖĞRÜÇ (Elsevier Science Bv, Po Box 211, 1000 AE Amsterdam, Netherlands, 2018)
Structural transformations of 3-fluorobenzaldehyde (C7H5FO, 3FBA) and 3-fluoro-4-methoxybenzaldehyde (C8H7FO2, 3F4MBA), taking place in different solid phase environments and at low temperature, were investigated by infrared spectroscopy, complemented by quantum chemistry calculations undertaken at the DFT(B3LYP)/6-311++G(d,p) level of approximation. The studied compounds were isolated from gas phase into cryogenic inert matrices (Ar, Xe), allowing to characterize their equilibrium conformational composition in gas-phase at room temperature. In both cases, two conformers differing by the orientation of the aldehyde moiety (with the carbonyl aldehyde bond as or trans in relation to the aromatic ring fluorine substituent) were found to coexist, with the as conformer being slightly more populated than the trans form. In situ narrowband UV irradiation of the as-deposited matrices led either to preferential isomerization of the as conformer into the trans form or decarbonylation of both conformers, depending on the used excitation wavelength. Deposition of the vapours of 3F4MBA only, onto the cold (15 K) substrate, produced an amorphous solid containing also both the as and trans conformers of the compound. Subsequent heating of the amorphous phase up to 268 K led to crystallization of the compound, which is accompanied by conformational selection, the as form being the single species present in the crystal. The experimentally observed transformations of the studied compounds, together with the structural and vibrational results obtained from the performed quantum chemical calculations, allowed a detailed structural and vibrational characterization of the individual conformers. (C) 2018 Elsevier B.V. All rights reserved.
Keywords: 3-Fluorobenzaldehyde; 3-Fluoro-4-methoxybenzaldehyde; Fluorobenzene; 2-Fluoro-methoxybenzene; Matrix-isolation and neat solid state low temperature IR spectroscopy; Quantum chemical calculations; Conformational isomerization; Photodecarbonylation; Molecular-Orbital Methods; Gaussian-Basis Sets; Conformational Isomerization; Transition-States; Matrix; Density; Fluorobenzaldehyde; Photochemistry; Spectra